KETERBATASAN RUANG KOTA MAGELANG: TANTANGAN TATA RUANG DAN ARAH KEBIJAKAN PENATAAN KAWASAN PERKOTAAN - Dwi Utari (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2026)
Magelang City faces spatial limitations that create pressure on residential areas, green open spaces (RTH), mobility, and public services. The primary challenge for a small city with a limited territorial area is to manage land use sustainably in order to preserve environmental quality and enhance the well-being of its residents. This study applies a descriptive qualitative approach based on a literature review of academic journals, institutional reports, and policy documents related to spatial utilization in Magelang City. Data analysis follows the Miles and Huberman model, involving data reduction, thematic data display, and conclusion drawing with verification. The results reveal that spatial constraints have led to increasing residential density, a declining proportion of green open spaces, greater pressure on basic infrastructure, and mobility congestion in certain areas. Population growth and land-use changes further intensify the risk of slum development and environmental degradation. These findings underscore the need for more efficient and sustainable spatial management strategies through vertical space utilization, revitalization of older urban areas, and strengthened land-use control to ensure controlled urban development. Policy recommendations include adopting the compact city concept, promoting vertical development, revitalizing densely populated areas, strengthening land-use regulation based on Detailed Spatial Plans (RDTR), and increasing as well as protecting the proportion of green open spaces to support environmental quality and urban welfare.